EXPERIENCE OF LAPAROSCOPIC CHOLECYSTECTOMY DURING A STEEP LEARNING CURVE AT A UNIVERSITY HOSPITAL - Ali, Syed Asad; Soomro, Abdul Ghani; Mohammad, Agha Taj; Jarwar, Mohammad; Siddique, Akmal Jamal (Journal of Ayub Medical College Abbottabad, 2012)
Background: Cholelithiasis is the most common disease of alimentary tract affecting the adult population globally and our country in particular is no exception to it as a cause of hospitalization. Surgical removal of gall bladder is the main stay of symptomatic cholelithiasis ensuring a permanent cure. The minimally invasive technique of laparoscopic cholecystectomy has gained wide acceptance as a Gold Standard treatment ever since its introduction. The purpose of this prospective observational study was to document our experience of laparoscopic Cholecystectomy during a learning curve in a single unit of a university hospital and compare it with other available data in the literature. Methods: Total 94 patients underwent laparoscopic cholecystectomy during the learning curve from Jan 2009 to Dec 2010 in the Department of Surgery Liaquat University Hospital Jamshoro. Results: Mean age was 42 years with females (88.29%) preponderance. Majority of the cases were operated by consultants (85.10%) within 25-60 minutes. Postoperative hospital stay was 3 days with return to work in 7 days. Only 6 (6.38%) cases were converted to open technique. Intra-peritoneal drains and Foley's catheter were kept in selected cases only. Eleven patients (11.70%) had intra-operative complications including complete transaction of CBD in only one (1.06%) male patient. Five patients (5.31%) had postoperative complications with two patients having iatrogenic duodenal injury which was not identified during surgery and pseudo cyst pancreas. Four patients (4.25%) died due to multiple organ failure. Conclusion: We conclude that Laparoscopic Cholecystectomy is a gold standard procedure and should be learned on virtual simulated models before starting this procedure on human patients. Keywords: Laparoscopic Cholecystectomy, Learning curve, experience.